METODE DALAM PROSES PEMBELAJARAN: Studi tentang Ragam dan Implementasinya - Kamsinah, Kamsinah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2008)
The study of various methods in the teaching process that supporting the educator to prepare and set achievement process of teaching goal. Teacher, mentor, and facilitator constitute one of the important factors to lead the learners to get better understanding about the material with various ways which have been decided systematically in situation and certain condition. Concerning with, it needs comprehensive understanding to set the use of a method in the teaching process. How variety with method implementation in the teaching process becomes explanation focus in this writing. The understanding and various methods from educational experts with its implementation description presented by hoping can be used to increase the learners’ interest, in order to make easy the goal achieve-ment suitable with subject matter in the teaching process. However, a material is good and complicated, but it is not supported by appro-priate strategy, method, or technique in its presenting will pass by without impression.